UNDERSTANDING COUNTRY RISK TOWARD FOREIGN DIRECT INVESTMENT MODERATED BY EASE OF DOING BUSINESS RANKING (Study in ASEAN (Indonesia, Malaysia, Thailand, Philippines, and Vietnam)) - Pertiwi, Nanda; Ratnawati, Kusuma; Aisjah, Siti (Universitas Brawijaya, Indonesia, 2020)
This research involves the phenomenon of Foreign Direct Investment. The purpose of this study is to analyze the determinants of country risk on Foreign Direct Investment (FDI), which is moderated by the rating of ease of doing business (EODB). The utilized sampling technique was purposive sampling. The objects of this research are Indonesia, Malaysia, Thailand, the Philippines, and Vietnam. Data analysis in this study utilized the Partial Least Squares (PLS) modeling approach. The results showed that 1) Political risk did not significantly influence FDI for Indonesia, Malaysia, and Vietnam, but did influence for Thailand and the Philippines. 2) Financial risk reflected by macroeconomic conditions significantly influenced Foreign Direct Investment for Indonesia, Malaysia, Thailand, the Philippines, and Vietnam. 3) The EODB rank moderated the influence of political risk on Foreign Direct Investment for Thailand but did not moderate for Indonesia, Malaysia, the Philippines, and Vietnam. 4) The EODB rating did not moderate the effect of financial risk on Foreign Direct Investment for all the studied countries. Finally, 5) the results of ranking the five studied countries based on country risk level from lowest to highest showed that Malaysia was first, followed by Thailand in second place, then the Philippines in third place and Vietnam in fourth, and the last was Indonesia in fifth (last) place. This means that Indonesia has the highest country risk value compared to the other ASEAN countries that became the objects of this research.